Analisis Kinerja Sosial dan Keuangan Lembaga Keuangan Mikro (LKM) Usaha Ekonomi Desa-Simpan Pinjam (UED-SP) Sinar Dana di Desa Sawah Kecamatan Kampar Utara Kabupaten Kampar - Khairani '; Ahmad Rifai; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to analyze social and financial performance of microfinance institutions UED-SP Sinar Dana. Social performance analyzed using Microfinance Information exchange (MIX) soscial performance standard report, and financial performance analyzed using 17 PEARLS ratio. Analysis of the UED-SP social peformance has reached the social mission and goals the cumulative volume of loans 25.10 percent, and the higher growth of loans volume is the agricultural sector 32.25 percent. The poor borrowers 23.33 percent and volume of loans increased 55.82 percent. Internal systems increased on a variety of loan products and increased incentives for staff. The output and outcome UED-SP was increasing in average annual, outreach of the women borrowers, the borrower of productive economic in the agricultural sector, poor borrowers, and the volume of saving. The financial performance of UED-SP obtained that the purpose of the protection is not achieved because it does not have a provision for loan losses on loans greater than 12 months delinquent. Effective financial structure is obtained the net loans highger than range limit of ideal accivement, ratio of members share capital in ideal, the ratio of capital institutions in ideal. Asset quality in non perfoaming loan and ratio of non-earning assets are in the ideal. Revenue and expenses earned operating costs and the ratio of net income are ideal. The ratio of income from loans and the current asset liquidity ratio are ideal. UED-SP showed signs of growth with the asset growth, loan growth, and savings deposit growth in not ideal ratio. Keywords: Financial Peformance, UED-SP, Social Peformance